2012
DOI: 10.1371/journal.pone.0048373
|View full text |Cite
|
Sign up to set email alerts
|

The τCstF-64 Polyadenylation Protein Controls Genome Expression in Testis

Abstract: The τCstF-64 polyadenylation protein (gene symbol Cstf2t) is a testis-expressed orthologue of CstF-64. Mice in which Cstf2t was knocked out had a phenotype that was only detected in meiotic and postmeiotic male germ cells, giving us the opportunity to examine CstF-64 function in an isolated developmental system. We performed massively parallel clonally amplified sequencing of cDNAs from testes of wild type and Cstf2t−/− mice. These results revealed that loss of τCstF-64 resulted in large-scale changes in patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…Targeted disruption of the testis-expressed polyadenylation gene Cstf2t resulted in severe male infertility, demonstrating a critical necessity for polyadenylation and mRNA processing in spermatogenesis [44, 45, 47]. The majority of the altered gene expression in spermatogenic cells in Cstf2t -/- mice is likely due to altered polyadenylation, but altered splicing [48] and genome expression [46] also contribute. Because τCstF-64 is expressed at high levels in brain as well as testis [4042], we wanted to determine whether Cstf2t influenced behavior as well as male fertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted disruption of the testis-expressed polyadenylation gene Cstf2t resulted in severe male infertility, demonstrating a critical necessity for polyadenylation and mRNA processing in spermatogenesis [44, 45, 47]. The majority of the altered gene expression in spermatogenic cells in Cstf2t -/- mice is likely due to altered polyadenylation, but altered splicing [48] and genome expression [46] also contribute. Because τCstF-64 is expressed at high levels in brain as well as testis [4042], we wanted to determine whether Cstf2t influenced behavior as well as male fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Given its role in control of global genome expression [46], it seems that Cstf2t could have profound epistatic effects on numerous functions, especially if the effects are on regulatory proteins with roles in chromatin expression. We have not yet uncovered a mechanism of how loss of the τCstF-64 polyadenylation protein might influence this type of behavior or why it might be most evident in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, 6) and therefore may have distinct functions in some aspects of mRNA 3 ′ processing or in other cellular processes. Indeed, a recent study reported differential expression of retrotransposon RNAs in the testis of CstF64τ knockout mice (Li et al 2012). Interestingly, the functional relationship between CstF64 and CstF64τ is reminiscent of that of PTB (or Ptbp1) and nPTB (or Ptbp2), two related hnRNPs that function in splicing regulation (Boutz et al 2007;CoutinhoMansfield et al 2007;Licatalosi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A second isoform of CstF-64, termed CstF-64, was found expressed mainly in brain and testis (106), and it has been implicated in modulating poly(A) site selection during spermatogenesis (107). Other studies, however, have revealed that CstF-64 is likely more broadly expressed, and may function redundantly with CstF-64 (2, 108).…”
Section: Cstfmentioning
confidence: 99%